1995
DOI: 10.1074/jbc.270.31.18593
|View full text |Cite
|
Sign up to set email alerts
|

αvβ5 Integrin Receptor-mediated Endocytosis of Vitronectin Is Protein Kinase C-dependent

Abstract: Previous studies have demonstrated that the alpha v beta 5 integrin receptor functions in the endocytosis and degradation of matrix-bound vitronectin by human skin fibroblasts (Panetti, T. S., and McKeown-Longo, P. J. (1993) J. Biol. Chem. 268, 11988-11993; Panetti, T. S., and McKeown-Longo, P. J. (1993) J. Biol. Chem. 268, 11492-11495). These earlier studies demonstrated that vitronectin degradation was inhibited by either antibodies to the beta 5 integrin or exogenous heparin, suggesting that both integrin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 47 publications
5
61
0
Order By: Relevance
“…These data as well as our previous data (58,60,88) indicate that vitronectin's basic domain may be , after which wells were blocked with 1% BSA for 1 h at 37 • C. HT-1080 cells that had been pretreated with and without sodium chlorate (CLO 3 ) for two days (see Materials and Methods) were lifted with Cellstripper TM , washed three times with DMEM/F12 containing 0.2% BSA, then seeded onto protein coated wells at 6 × 10 5 cell/ml. Cells were allowed to adhere for 1 h at 37 • C, then washed with PBS and fixed in 3% paraformaldehyde.…”
Section: Vitronectin's Basic Domain Mediates Syndecan Dependent Cell supporting
confidence: 73%
See 1 more Smart Citation
“…These data as well as our previous data (58,60,88) indicate that vitronectin's basic domain may be , after which wells were blocked with 1% BSA for 1 h at 37 • C. HT-1080 cells that had been pretreated with and without sodium chlorate (CLO 3 ) for two days (see Materials and Methods) were lifted with Cellstripper TM , washed three times with DMEM/F12 containing 0.2% BSA, then seeded onto protein coated wells at 6 × 10 5 cell/ml. Cells were allowed to adhere for 1 h at 37 • C, then washed with PBS and fixed in 3% paraformaldehyde.…”
Section: Vitronectin's Basic Domain Mediates Syndecan Dependent Cell supporting
confidence: 73%
“…Previous studies from our laboratory have shown that vitronectin degradation is dependent upon an RGD mediated interaction with integrin αvβ5 (49,59) and is sensitive to the addition of exogenous heparin, as well as treatment with sodium chlorate or heparitinase (60,88), suggesting that vitronectin's turnover is also dependent upon its interaction with a heparan sulfate proteoglycan. To determine whether vitronectin's basic domain is required for its turnover from the extracellular environment, HT-1080 cell layers were incubated with increasing concentrations of 125 I labeled rVn and assayed to determine the level of binding and degradation.…”
Section: Vitronectin's Basic Domain Is Required For Vitronectin Turnovermentioning
confidence: 99%
“…There are several reports that fibrinogen bound to the surfaces of A549 cells is internalized by endocytosis via RGD-dependent binding to integrin ␣ v ␤ 3 (65). Additionally, the internalization and degradation of matrix-bound vitronectin are mediated by integrin ␣ v ␤ 5 and involve protein kinase C (66). Integrin ␣ v ␤ 5 is internalized in its active, vitronectinbound form (67, 68) through clathrin-coated pits (69).…”
Section: Pharmacoproteomic Analysis Of P11mentioning
confidence: 99%
“…Given the significant roles of PKC in the modulation of phagocytosis in other cell types [17][18][19] and the unique effects of PMA, a PKC activator, on the cytoskeletal rearrangement in mast cells [16], it is likely that PKC may modulate bacterial internalization by mast cells. To investigate the roles of PKC in FimH ϩ E. coli internalization by HMC-1 5C6 cells, we used PMA, a well-characterized activator for cPKC and nPKC members, to stimulate mast cells for 1 h. The activator was then completely removed by washing before adding bacteria.…”
Section: Involvement Of Pkc In Bacterial Internalizationmentioning
confidence: 99%
“…Its activation induces a pattern of cytoskeletal rearrangement in mast cells that is quite different from that seen in other cell types [16]. Moreover, it is known that PKC facilitates several internalization processes including Fc␥ receptor-mediated phagocytosis in monocytes [17], integrin receptor-mediated endocytosis in fibroblasts [18], and oxidant-dependent ingestion of IgGopsonized targets in neutrophils [19]. However, it is also noteworthy that PKC has been reported to down-regulate a number of internalization processes such as phagocytosis of zymosan by macrophages [20].…”
Section: Introductionmentioning
confidence: 99%